2015
DOI: 10.1121/1.4923359
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of speech rhythm in a second language by learners with rhythmically different native languages

Abstract: The development of speech rhythm in second language (L2) acquisition was investigated. Speech rhythm was defined as durational variability that can be captured by the interval-based rhythm metrics. These metrics were used to examine the differences in durational variability between proficiency levels in L2 English spoken by French and German learners. The results reveal that durational variability increased as L2 acquisition progressed in both groups of learners. This indicates that speech rhythm in L2 English… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 35 publications
4
49
1
2
Order By: Relevance
“…This is a small subset of a larger corpus of L2 speech collected and described by Ordin et al (2015a;2015b consisted of two parts: interview and sentence elicitation task. During the first part, the participants were asked ten questions -the same set of questions for every speaker -related to personal biography, music and reading preferences, educational choices, etc.…”
Section: Methods Speech Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a small subset of a larger corpus of L2 speech collected and described by Ordin et al (2015a;2015b consisted of two parts: interview and sentence elicitation task. During the first part, the participants were asked ten questions -the same set of questions for every speaker -related to personal biography, music and reading preferences, educational choices, etc.…”
Section: Methods Speech Materialsmentioning
confidence: 99%
“…More proficient L2 learners of English tend to deliver L2 speech at faster rates compared to less proficient speakers (Anderson-Hsieh and Venkatagiri, 1994;Ordin and Polyansksaya, 2015a;2015b). Ordin and Polyanskaya (2015b) compared speech rate in the same set of sentences produced by French and German learners of English at different proficiency levels.…”
Section: Cross-linguistic and Developmental Differences In Speech Ratmentioning
confidence: 99%
See 1 more Smart Citation
“…Addressing this broad research issue requires an exploration of the development of speech rhythm during the course of first and second language acquisition in humans and development of rhythm in communicative signals emitted by nonhuman animals. Earlier studies showed that speech rhythm develops from more regular (isochroneous, with quasi‐equal syllable and vowel durations) toward more irregular rhythmic patterns, and that this trajectory is typical of both first and second language acquisition . The development of speech rhythm in language acquisition is governed not only by language‐specific, and thus culturally transmitted factors (i.e., dominant rhythmic patterns in the native language of an adult learning a second language), but also by universal factors (i.e., by mechanical constraints on speech production and the properties of the mammalian auditory system).…”
Section: Development In Ontogenesismentioning
confidence: 99%
“…Earlier studies showed that speech rhythm develops from more regular (isochroneous, with quasi-equal syllable and vowel durations) toward more irregular rhythmic patterns, and that this trajectory is typical of both first and second language acquisition. [10][11][12][13] The development of speech rhythm in language acquisition is governed not only by language-specific, and thus culturally transmitted factors (i.e., dominant rhythmic patterns in the native language of an adult learning a second language), but also by universal factors (i.e., by mechanical constraints on speech production and the properties of the mammalian auditory system). Thus, adult native speakers of languages that exhibit irregular rhythmic patterns cannot simply transfer these rhythmic skills from their native to a second language, but have to develop the required degree of irregularity anew, similar to the way that children develop rhythmic skill in their first language.…”
Section: Development In Ontogenesismentioning
confidence: 99%